Comparison of short-term clinical outcomes between low-dose prasugrel and clopidogrel as part of triple antithrombotic therapy in patients requiring oral anticoagulant therapy and percutaneous coronary intervention. - Hideki Kitahara; Kazuya Tateishi; Yuki Shiko; Yusuke Inaba; Yoshio Kobayashi; Takahiro Inoue (PLoS ONE, 2022)
Background Triple antithrombotic therapy, including dual antiplatelet therapy and oral anticoagulant (OAC), is recommended for a short-term period after percutaneous coronary intervention (PCI) in patients requiring anticoagulation therapy. The purpose of this study was to compare in-hospital clinical outcomes between low-dose prasugrel (3.75 mg/day) and clopidogrel, as part of triple antithrombotic therapy, using a large database in Japan. Methods Patients with ischemic heart disease who underwent PCI between January 2015 and December 2019, and were prescribed triple therapy with aspirin, a P2Y12 inhibitor (clopidogrel or low-dose prasugrel), and OAC (direct oral anticoagulant: DOAC or vitamin K antagonist: VKA), were selected from the Diagnosis Procedure Combination database. The primary outcome was in-hospital mortality. The secondary outcomes were myocardial infarction, ischemic stroke, bleeding stroke, gastrointestinal bleeding, and blood transfusion. Results Overall, 5,777 patients were eligible in this analysis. The patients were divided into 4 subgroups according to the type of P2Y12 inhibitor and OAC: clopidogrel/DOAC (n = 1,628), clopidogrel/VKA (n = 1,334), prasugrel/DOAC (n = 1,607), and prasugrel/VKA (n = 1,208). There was no significant difference in the incidence of death and gastrointestinal bleeding among the 4 subgroups. The prasugrel/DOAC group had significantly lower incidence of MI (OR 0.566, 95% CI 0.348-0.921). The incidence of ischemic stroke was significantly lower in the prasugrel/DOAC group (OR 0.701, 95% CI 0.502-0.979), and significantly higher in the clopidogrel/VKA group (OR 1.680, 95% CI 1.273-2.216). Need for blood transfusion was less frequent in the prasugrel/DOAC group (OR 0.729, 95% CI 0.598-0.890), and more frequent in both the clopidogrel/VKA group (OR 1.424, 95% CI 1.187-1.708) and the prasugrel/VKA group (OR 1.633, 95% CI 1.367-1.950). Conclusions Combination of low-dose prasugrel and DOAC was associated with lower incidence of MI, ischemic stroke, and blood transfusion. Low-dose prasugrel may be feasible as part of triple therapy in patients undergoing PCI.